STRATEGI PROMOSI PENJUALAN RITEL TRADISIONAL (Studi Pada Pedagang Sembako Pasar Karangsambung) - Fitra, Joko (P4M STIE Putra Bangsa, 2017)
This study examines the sales promotion strategies undertaken by traditional retailers, in this case in the Market merchants Karangsambung groceries. Some of the strategies offered by marketing experts may be modified by traders in the Market groceries Karangsambung in promoting the products sold. This is done because of limited resources owned by the merchant. This research approach uses qualitative descriptive approach. The data collection technique using observation, in-depth interview techniques, and the library to study and documentation. Decision informants conducted by using informants aims. Analysis of the data using analytical models Miles and Huberman comprising the steps of data collection, data reduction, data presentation, and conclusion. The results showed that the basic needs trader in the Market Karangsambung keep doing sales promotion in the form of point of purchase, samples, loyalty programs, direct gifts, and gifts for referrals. Implementation of sales promotion conducted by the merchant groceries market Karangsambung influenced by several things such as Marketers (Knowledge and market network owned by the merchant), the availability of marketing costs, the nature of the market (broad market geographically, the market concentration, and the type of buyer), as well as the types of products traded.